Impacts of the MSU-Sulu College of Agriculture Patikul Extension Program on Students Residing within the Municipality of Patikul - . Sammah, Merhama M; Marajuli, Fatima Sheirene M.; Sammah, Ronnie H.; Ahajani, Nedzfa A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study focused on the positive impact of the Patikul Ex-tension Program of MSU-Sulu College of Agriculture on the enrolled students residing within the boundaries of Patikul Municipality. Specifically, the study assessed the impacts of the program in three areas: Socio-Cultural, Economic, and Envi-ronmental aspects. To gather the necessary data, the re-searchers used a self-devised structured survey questionnaire, which underwent a reliability test. The questionnaire consist-ed of two parts. The first part determined the profile of the respondents using the quantitative descriptive method of fre-quency distribution. The second part assessed the impact of the program through selected questions, with the data ana-lyzed using weighted means and inferential statistics. A one-way ANOVA was employed to examine the significant differ-ences in the responses across different respondent profiles.Results showed that most of the respondents were 25 years old or older, female, first-year students, and residents of Patikul, Sulu, aged 21 or above. In terms of impact, the Socio-Cultural aspect had a weighted mean of 4.58, interpreted as "Strongly Agree"; the Economic aspect had a weighted mean of 4.42, interpreted as "Agree"; and the Environmental aspect had a weighted mean of 4.46, interpreted as "Agree." Regard-ing significant differences, the responses on the Socio-Cultural, Economic, and Environmental impacts of the Patikul Exten-sion Program varied across the profiles, with the results being mostly significant according to the one-way ANOVA test.Based on these findings, the researchers recommend the con-tinuous development of the program through faculty devel-opment, additional facilities, and laboratory improvements, as well as conducting further studies on the impact of faculty de-velopment on the stakeholders of the institution.